PENGARUH CUSTOMER RATING, CUSTOMER REVIEWS, PRUDUCT QUALITY, DAN LIVE STREAMING, TERHADAP PURCHASE DECISION DI TIKTOK SHOP - Erni Setiawati; Mardiono; Irwansyah (OBOR: Oikonomia Borneo, 2025)
This study aims to determine the simultaneous and partial influence of Customer Rating (X1), Customer Reviews (X2), Product Quality (X3), and Live Streaming (X4) on Purchase Decisions (Y) on TikTok Shop in Samarinda City. The research employs a quantitative approach with purposive sampling, collecting data from 150 respondents. Data analysis includes data quality tests, classical assumption tests, multiple linear regression analysis, correlation coefficient (R), coefficient of determination (R²), and hypothesis testing (F-test and T-test). The multiple linear regression equation results show: Y = a + 0.328(X1) + 0.306(X2) + 0.367(X3) + 0.258(X4). The correlation test indicates a strong relationship between the independent variables and Purchase Decision, with a correlation coefficient (R) of 0.924. The coefficient of determination (R²) is 85.4%, indicating that Customer Rating, Customer Reviews, Product Quality, and Live Streaming collectively influence Purchase Decision by 85.4%, while the remaining 14.6% is influenced by other factors outside the model. The T-test results demonstrate that Customer Rating, Customer Reviews, Product Quality, and Live Streaming each have a significant effect on Purchase Decision. Additionally, the F-test confirms that all four variables simultaneously have a significant influence on Purchase Decision on TikTok Shop